Framing the Text: The Year 2000 in British Columbia - Harker, W. John (Canadian Journal of Education/Revue canadienne de l’éducation, 1992)
This paper presents an analysis of the text, intertext, and subtext of the Year 2000 document, a comprehensive statement of policies and objectives for education in British Columbia issued by the Ministry of Education in 1990. Examination of the relationships between the text and intertext of the Year 2000 reveals a subtext that fundamentally contradicts the stated objectives of the document itself. Rather than encouraging the development of students’ individu- ality, as the text of the Year 2000 document frequently advocates, its subtext reveals an educational agenda that would maintain social stability and economic prosperity at the expense of students’ individuality. The impossibility of a text imposing such control is discussed. Cet article présente une analyse du texte, de l’“intertexte” et du “sous-texte” de Year 2000, un document préparé en 1990 par le ministère de l’Éducation de la Colombie-Britannique et dans lequel sont énoncées de façon détaillée ses politi- ques et objectifs pédagogiques. L’examen des relations entre le texte et l’inter- texte révèle un sous-texte qui contredit fondamentalement les objectifs énoncés dans le document lui-même. Plutôt que d’encourager l’épanouissement de l’indi- vidualité des élèves, comme le prône à maintes reprises le texte de Year 2000, le sous-texte révèle un programme éducatif qui maintient la stabilité sociale et la prospérité économique aux dépens de l’individualité des élèves.